Implementasi Peraturan Bupati Karanganyar Nomer 82 Tahun 2019 Tentang Petunjuk Pelaksanaan Penyelenggaraan Administrasi Kependudukan Di Kecamatan Kebakkramat Kabupaten Karanganyar - Saputra, Fadhilah Rizky; Suranto, Joko; Sugiyarti, Sri Riris (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Karanganyar Regent Regulation Number 82 of 2019 concerning Guidelines forImplementing Population Administration in Kebakkramat District, KaranganyarRegency is one of the guidelines to make it easier for the Population and CivilRegistration Service to carry out services related to Population Administration. Thisresearch aims to analyze and describe the implementation of Karanganyar RegentRegulation Number 82 of 2019 concerning Guidelines for Implementing PopulationAdministration in Kebakkramat District, Karanganyar Regency. There are still people inKebakkramat District who don't understand the importance of e-KTP, even the youngergeneration doesn't understand the importance of e-KTP, and many people are too lazy tocome directly to the Kebakkramat District office, usually just leaving the house. files toemployees and usually people give bribes in the form of money to employees so that theprocess of making e-KTPs is accelerated.. The research method used is descriptiveresearch with a qualitative approach. Data collection was carried out using interview,observation and documentation techniques . This research analysis uses four elements,namely data collection, data reduction, and drawing conclusions.The technique fordetermining informants for this research uses purposive sampling and snowball samplingtechniques. The informants in this research were 5 people consisting of the KebakkramatDistrict Secretary, the governance section, the e-KTP maker operator and theKebakkramat community. The results of the research conducted by the author show thatthe e-KTP making service in Kebakkramat District can be said to be good, although thereis some confusion and misunderstanding regarding social media and informationsources.Keywords: Communication, Resources, Disposition, and Bureaucratic Structure